Sublingual grass and ragweed immunotherapy: Clinical considerations$da PRACTALL consensus report - Li, James T.; Pfaar, Oliver (The journal of allergy and clinical immunology, 2016)
Sublingual allergen immunotherapy provides a new option for patients with allergic rhinitis in the United States. The efficacy of these sublingual immunotherapy tablets in the treatment of allergic rhinitis has been firmly established in large multicenter clinical trials. In addition, the clinical benefits of sublingual immunotherapy might persist after treatment is discontinued. Local reactions, such as gastrointestinal or oropharyngeal symptoms, are common. However, severe anaphylaxis is rare, and therefore the immunotherapy tablets can be administered at home. Sublingual immunotherapy for allergic rhinitis has been used successfully for years in Europe, and these products might be appropriate for patients who do not do well with standard drug therapy or for those who prefer a disease-modifying approach.
Gesehen am 01.02.2019
Available online September 12, 2015